2016
DOI: 10.1371/journal.pone.0148784
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Effect of Anti-Angiogenic and Radiation Therapy: Quantitative Evaluation with Dynamic Contrast Enhanced MR Imaging

Abstract: PurposeWe assessed the effects of anti-angiogenic therapy (AAT) on radiation therapy (RT), evaluating the tumor growth and perfusion patterns on dynamic contrast enhanced MR (DCE-MR) images.MethodsThirteen nude mice with heterotopic xenograft cancer of human lung cancer cell line were used. To observe the interval change of the tumor size and demonstrate the time-signal intensity enhancement curve of the tumor, the mice were subdivided into four groups: control (n = 2), AAT (n = 2), RT (n = 5), and combined th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 26 publications
1
3
0
Order By: Relevance
“…Liu et al (Liu et al 2020) evaluated the therapeutic effect of radiotherapy combined with apatinib (anti-angiogenesis drug) on mouse nasopharyngeal carcinoma xenograft model, and found that the tumor inhibition effect of combined therapy was stronger than that of apatinib alone or radiotherapy alone. This is similar to the research results of Koo et al (Koo et al 2016) and Gao et al (Gao et al 2015), which all indicate the synergistic effect of anti-angiogenesis therapy on radiotherapy. Moreover, compared with radiotherapy and chemotherapy, the tumor volume of patients with non-small cell lung cancer with multiple brain metastases after whole brain irradiation combined with apatinib is signi cantly reduced, and patients can get better objective remission rate and longer median progression-free survival time, but there is no signi cant difference in median overall survival time (Ren et al 2021).…”
Section: Discussionsupporting
confidence: 92%
“…Liu et al (Liu et al 2020) evaluated the therapeutic effect of radiotherapy combined with apatinib (anti-angiogenesis drug) on mouse nasopharyngeal carcinoma xenograft model, and found that the tumor inhibition effect of combined therapy was stronger than that of apatinib alone or radiotherapy alone. This is similar to the research results of Koo et al (Koo et al 2016) and Gao et al (Gao et al 2015), which all indicate the synergistic effect of anti-angiogenesis therapy on radiotherapy. Moreover, compared with radiotherapy and chemotherapy, the tumor volume of patients with non-small cell lung cancer with multiple brain metastases after whole brain irradiation combined with apatinib is signi cantly reduced, and patients can get better objective remission rate and longer median progression-free survival time, but there is no signi cant difference in median overall survival time (Ren et al 2021).…”
Section: Discussionsupporting
confidence: 92%
“…To improve blood perfusion and thus tumor oxygenation, again vascular normalization using anti-angiogenic-therapy was suggested ( 103 , 104 ). According to this hypothesis Koo et al recently showed that a combined radiotherapy and anti-angiogenic treatment (with the second-generation multi-targeted receptor tyrosine kinase inhibitor sunitinib malate, which inhibits PDGF and VEGF) showed synergistic effects in anti-cancer treatment using heterotopic human lung cancer xenografts ( 105 ). Herein, radiation induced extensive necrosis in the central portion of the tumors, as the immature tumor blood vessels were sensitive to radiotherapy.…”
Section: Tumor Endothelium Mediated Immunological Consequences In Thementioning
confidence: 99%
“…When radiotherapy was then combined with anti-angiogenic treatment that inhibits the formation of immature blood vessels, the tumor perfusion was maintained and tumor necrosis was reduced. This treatment combination resulted then in a more significantly suppressed tumor growth, as vessel normalization, which achieved an efficient tumor perfusion, significantly improved tumor oxygenation that is prerequisite for the tumoricidal effects of ionizing radiation ( 105 ). In line with these findings Zhu et al could show that inhibition of hypoxia-induced angiogenesis limits the efficiency of radiotherapy ( 106 ).…”
Section: Tumor Endothelium Mediated Immunological Consequences In Thementioning
confidence: 99%
“…Antiangiogenic drugs possess the ability to selectively target and inhibit the growth of neovascularization, thereby modulating blood flow and oxygenation within tumor tissues. This phenomenon results in the reoxygenation of hypoxic tumor tissues, consequently enhancing the radiosensitivity of these tissues [11,12]. Presently, both domestic and international efforts have been directed toward exploring a combined antitumor approach involving radiotherapy and antiangiogenesis therapy.…”
Section: Discussionmentioning
confidence: 99%